Museum Fotografi Solo (Penekanan pada aspek green architecture) - Adi Irawan, Muhammad; , Dr. Ir Dhani Mutiari, MT; , Nur Rahmawati, ST, MT (2015)
The museum is a storage place various objects and historic documents. In addition the museum also berfungis as educational media from various heritage and relics of the maestro art. Planning a solo photography museum meruapakan a container for all photography. The purpose of such planning is as a container of all photographic activity that can provide advantages other than as a tourist attraction as well as a vehicle of education for beginners and professionals. In the museum tredapat various collections including the permanent collection chamber that stores various photographic work of professionals and masters the art of photography, while the temporary area is a weekly show off zone for beginners. Designing a solo photography museum located in Jalan Colonel Sutarto, Jebres, Sukoharjo. Museum building stands on an area of 24000 m2 pants, with an area of 16000 m2 awakened, while other land is also berfungis landscape area as a green element and education for the photographer to look for the best view. Museum building using the concept of cubism form with the game back and forth form a circle and a triangle with the concept of the facade blend of green architecture and metaphor symbol landscape photography as well as structuring a public space as an area that supports the whole building.